Silicon Carbide Ceramics
SiC ceramics with a surface modified layer derived from their raw materials provide self-healing and enhanced environmental resistance by forming silicates, addressing adhesion and durability issues in existing coatings.
Patent Information
- Application Number
- JP2019518774
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-05-15
- Filing Date
- 2018-05-14
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2038-05-14
AI Technical Summary
Existing silicon carbide (SiC) ceramic coatings lack sufficient adhesion to the base material, leading to peeling and impaired environmental resistance, and do not exhibit self-repair capabilities when damaged.
The SiC ceramics incorporate a surface modified layer containing silicate, derived from the raw materials used to form the base material, which forms a new layer upon damage without external supply, utilizing metal oxides like scandium oxide and yttrium oxide to create silicates through oxidation.
The SiC ceramics achieve excellent environmental protection coatings with self-healing properties, maintaining durability in harsh environments such as high-temperature steam, and eliminating the need for external repairs.
Smart Images

Figure 0007599674000001 
Figure 0007599674000002 
Figure 0007599674000003
Abstract
Description
[Technical field]
[0001] The present invention relates to silicon carbide ceramics. [Background technology]
[0002] Ceramic materials (hereinafter referred to as "SiC ceramic materials") made of silicon carbide (hereinafter referred to as "SiC ceramic materials") have excellent physical properties such as light weight, heat resistance (high temperature strength), wear resistance (high hardness), chemical stability (oxidation resistance, corrosion resistance, etc.), high thermal conductivity, low thermal expansion coefficient, low induced radiation, and low decay heat. In the aerospace field, SiC ceramic materials are used in engines, and aircraft development using SiC ceramic materials as aircraft materials is underway. In the nuclear field, the application of SiC ceramic materials to fuel cladding tubes, etc. is being considered with the aim of reducing the risk of hydrogen explosions.
[0003] Conventionally, a technique has been disclosed in which a rare earth silicate film is formed on a ceramic substrate by a sol-gel method using rare earth nitrate hydrate and tetraethoxysilane as starting materials, and the coated film is then heat-treated (Patent Document 1). Patent Document 1 employs the sol-gel method to form a film on a ceramic substrate, and actually only discloses silicon nitride ceramics as the ceramic substrate. However, the film formation technique using the sol-gel method disclosed in Patent Document 1, or a general film formation technique using plasma spraying, etc., cannot form a sufficiently dense film, and the adhesion between the formed film and the ceramic substrate (base material) is not high, resulting in problems such as peeling of the coating and impaired environmental resistance characteristics.
[0004] In the technology of Patent Document 1, after a silicon carbide ceramic substrate is formed, a water vapor corrosion-resistant coating made of rare earth silicate is formed on the surface of the substrate by a sol-gel method using rare earth nitrate hydrate and tetraethoxysilane as starting materials. With this technology, if the water vapor corrosion-resistant coating is damaged, such as peeled off, it is not possible to expect the water vapor corrosion-resistant coating to self-repair unless the rare earth metal component that is the raw material for the rare earth silicate is supplied from the outside, for example by subjecting the damaged portion to the sol-gel method again.
[0005] The inventors have previously developed a SiC fiber-reinforced SiC composite material (hereinafter also referred to as "SiC / SiC composite material") that includes a multiphase matrix containing a SiC phase and a phase of a substance that is less reactive to SiC, and SiC fibers arranged in the matrix (Patent Document 2).
[0006] This SiC / SiC composite material has improved toughness of SiC ceramics by combining it with SiC fibers, and has excellent durability because oxidation is suppressed by the formation of an oxide film of silica even in high-temperature oxidizing atmospheres. However, even with this SiC / SiC composite material, there was room for improvement in terms of maintaining durability in environments where silica reacts, such as high-temperature steam. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2004-299948 A [Patent Document 2] International Publication WO2016 / 093360A1 Summary of the Invention [Problem to be solved by the invention]
[0008] It is an object of the present invention to provide a SiC ceramic having an excellent environmental barrier coating. [Means for solving the problem]
[0009] The present invention relates to the following silicon carbide (SiC) ceramic. The SiC ceramic of the present invention has a feature that it contains a surface-modified layer containing a metal oxide and a silicate, and the surface-modified layer is derived from the raw material for forming the SiC ceramic, which is the base material. Therefore, even if the damage of the surface-modified layer reaches the base material, the SiC ceramic exhibits a self-repairing property of forming a new surface-modified layer without the need to supply material from outside.
[0010] Section 1. A silicon carbide ceramic containing a metal oxide, a surface modification layer including a silicate; The surface modification layer is derived from the raw material of the silicon carbide ceramics, which is the base material. 1. A silicon carbide ceramic comprising:
[0011] Section 2. 2. The silicon carbide ceramic according to claim 1, wherein the surface modification layer contains 50% by weight or more of silicate.
[0012] Section 3. 3. The silicon carbide ceramic according to claim 1 or 2, wherein the surface modification layer containing the silicate is formed in the vicinity of the surface of the silicon carbide ceramic base material.
[0013] Section 4. 4. The silicon carbide ceramic according to any one of items 1 to 3, wherein the metal oxide is at least one metal oxide selected from the group consisting of scandium oxide (Sc2O3), yttrium oxide (Y2O3), erbium oxide (Er2O3), ytterbium oxide (Yb2O3), alumina (Al2O3) and lutetium oxide (Lu2O3).
[0014] Section 5. 5. The silicon carbide ceramic according to any one of items 1 to 4, wherein the silicate is at least one silicate selected from the group consisting of scandium silicate (Sc2Si2O7), yttrium silicate (Y2SiO5), erbium silicate (ErSiO5), ytterbium silicate (Yb2SiO5), ytterbium silicate (Yb2Si2O7), aluminum silicate (Al2SiO5), and lutetium silicate (LuSiO5).
[0015] Section 6. 1. A method for producing silicon carbide ceramics, comprising: (1) dispersing a silicon carbide-forming raw material and a metal oxide in a dispersion medium; (2) sintering the dispersion obtained in step (1); (3) heat-treating the sintered product obtained in step (2) to form a surface-modified layer containing silicate on the silicon carbide ceramic base material; The method according to claim 1, further comprising:
[0016] Section 7. 7. The method according to claim 6, wherein the surface modification layer contains 50% by weight or more of silicate.
[0017] Section 8. 9. The method according to item 7 or 8, wherein the step (3) is a step of heat-treating the sintered product obtained in the step (2) to form a surface-modified layer containing a silicate near the surface of the silicon carbide ceramic base material.
[0018] Section 9. 9. The method according to any one of items 6 to 8, wherein the metal oxide is at least one oxide selected from the group consisting of scandium oxide (Sc2O3), yttrium oxide (Y2O3), erbium oxide (Er2O3), ytterbium oxide (Yb2O3), alumina (Al2O3) and lutetium oxide (Lu2O3).
[0019] Section 10. 10. The method according to any one of items 6 to 9, wherein the silicate is at least one silicate selected from the group consisting of scandium silicate (Sc2Si2O7), yttrium silicate (Y2SiO5), erbium silicate (ErSiO5), ytterbium silicate (Yb2SiO5), ytterbium silicate (Yb2Si2O7), aluminum silicate (Al2SiO5), and lutetium silicate (LuSiO5).
[0020] Section 11. 6. A ceramic fiber-reinforced silicon carbide composite material comprising the silicon carbide ceramic according to any one of items 1 to 5 as a base material and ceramic fibers.
[0021] Section 12. 12. The ceramic fiber-reinforced silicon carbide composite material according to item 11, wherein the ceramic fiber is at least one type of ceramic fiber selected from the group consisting of silicon carbide fiber, alumina fiber, and carbon fiber. Effect of the Invention
[0022] The SiC ceramics containing the metal oxide of the present invention have an excellent environmental resistance coating. The SiC ceramics containing the metal oxide of the present invention have a surface modification layer containing silicate, and the surface modification layer is derived from the raw material of the silicon carbide ceramic base material, and therefore has excellent self-repairing properties. [Brief description of the drawings]
[0023] [Figure 1] 1 is a diagram showing an embodiment of a method for producing SiC ceramics according to the present invention. [Diagram 2] FIG. 13 is a diagram showing a comparison of liquid phase sintered SiC containing Yb2O3 according to an embodiment after heat treatment (1,350°C-24h). [Diagram 3] FIG. 1 is a diagram showing the structure of liquid phase sintered SiC containing Yb2O3 according to an embodiment after heat treatment (20 wt% material, 1,350° C.-24 h). [Figure 4]FIG. 13 is a diagram showing a composition analysis of liquid phase sintered SiC containing Yb2O3 according to an embodiment after heat treatment (20 wt% material, 1,350° C.-24 h). [Diagram 5] FIG. 13 is a diagram showing a composition analysis (1,350° C.-24 h) of the reaction sintered SiC containing Yb2O3 of the embodiment after heat treatment. [Figure 6] FIG. 1 shows a composition analysis (1,500° C.-100 h) of a liquid phase sintered SiC fiber reinforced composite material containing Yb2O3 according to an embodiment of the present invention after heat treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] [1] SiC ceramics The silicon carbide (SiC) ceramic of the present invention is A SiC ceramic containing a metal oxide, a surface modification layer including a silicate; The surface modification layer is derived from the raw material of the SiC ceramics, which is the base material. It is characterized by:
[0025] In the SiC ceramic of the present invention, the surface modification layer is formed by the reaction between the silica formed on the surface by the oxidation of SiC contained in the base material and the contained metal oxide. In other words, the raw material of the surface modification layer is contained in the base material SiC ceramic, and thus exhibits self-repairing properties. The self-repairing properties are an effect that, since the surface modification layer originates from the raw material of the base material SiC ceramic, even if the damage of the surface modification layer reaches the base material in an oxidizing atmosphere under a real environment such as high-temperature oxidation or high-temperature steam, a new surface modification layer is formed at the location where the damage occurred by the reaction between new silica generated by the oxidation of SiC and the contained metal oxide without the need to supply material from outside.
[0026] The SiC ceramic of the present invention undergoes a dispersion process and a sintering process as described later in the manufacturing method, and then an oxidation heat treatment process is performed in which the SiC contained in the base material is oxidized on the surface of the ceramic to produce silica (SiO2). This silica (SiO2) then reacts with the metal oxide (Yb2O3, etc.) contained in the base material to form a surface-modified layer of silicate (silicates such as Yb2SiO5 and Yb2Si2O7) near the surface of the ceramic. In this way, a surface-modified layer containing dense silicate, the components of which are derived from the raw materials forming the SiC ceramic base material, is formed on the surface of the SiC ceramic base material.
[0027] In the SiC ceramic of the present invention, the raw material for forming the surface modification layer mainly contains SiC as the main material, and an added metal oxide (Yb2O3, Y2O3, etc.), etc.
[0028] (1) Silicon carbide (SiC) As described later in the manufacturing method, SiC powder can be used as the SiC component for forming SiC ceramics. When using the reaction sintering method, SiC powder, C powder, and Si powder are mixed and used as the raw material for forming silicon carbide.
[0029] (2) Metal oxides The metal oxide is preferably at least one metal oxide selected from the group consisting of scandium oxide (Sc2O3), yttrium oxide (Y2O3), erbium oxide (Er2O3), ytterbium oxide (Yb2O3), alumina (Al2O3) and lutetium oxide (Lu2O3). The metal oxide is more preferably ytterbium oxide (Yb2O3), alumina (Al2O3) or the like.
[0030] The metal oxide may be used alone or in combination of two or more kinds.
[0031] (3) Surface modification layer containing silicate The silicate contained in the surface modification layer of the SiC ceramic is preferably at least one silicate selected from the group consisting of scandium silicate (Sc2Si2O7), yttrium silicate (Y2SiO5), erbium silicate (ErSiO5), ytterbium silicate (Yb2SiO5), ytterbium silicate (Yb2Si2O7), aluminum silicate (Al2SiO5), and lutetium silicate (LuSiO5).
[0032] The silicate is preferably at least one rare earth element silicate selected from the group consisting of ytterbium silicate (Yb2SiO5) and ytterbium silicate (Yb2Si2O7), or aluminum silicate (Al2SiO5). In addition, the silicate may be various silicates such as magnesium silicate, barium-strontium aluminosilicate (BSAS), or the like.
[0033] Silicates have excellent heat and environmental resistance, and their thermal expansion coefficient is 3 to 8[×10 -6 / K]. This thermal expansion coefficient indicates the rate at which an object expands due to an increase in temperature per unit of temperature, and is expressed in units per Kelvin ( / K) according to the JIS standard.
[0034] The silicate may be of one type alone or of two or more types.
[0035] The surface modification layer of the SiC ceramic, including the silicate (Yb2SiO5, Yb2Si2O7, etc.) constituting it, originates from the raw material of the SiC ceramic, which is the base material. Considering the environmental resistance of the SiC ceramic of the present invention, the surface modification layer may contain silicate. The surface modification layer preferably contains 50% by weight or more of silicate, in that the silicon carbide ceramic obtained has excellent heat resistance and environmental resistance. The upper limit of the content of silicate contained in the surface modification layer is close to 100% by weight. In this case, the surface modification layer is substantially composed of silicate. The surface modification layer preferably contains 50 to 100% by weight of silicate. In addition, the surface modification layer preferably contains 100% by weight of silicate, but may contain 50 to 80% by weight of silicate.
[0036] According to the manufacturing method described later, by heat treating the SiC ceramics as the base material, a surface-modified layer containing silicate is generated near (or on) the surface of the SiC ceramics. The amount of the surface-modified layer containing silicate formed on the SiC ceramics is not particularly limited, but the amount is optimized according to the environment in which the SiC ceramic member is used. The thickness of the surface-modified layer containing silicate on the SiC is optimally designed according to the member to which it is applied. It is also possible to form the surface-modified layer containing silicate to a thickness of, for example, about 100 μm. The thickness of the surface-modified layer containing silicate may be about 1 to 50 μm or about 2 to 20 μm.
[0037] In the SiC ceramic of the present invention, a surface modification layer containing silicate (Yb2SiO5, Yb2Si2O7, etc.) is formed by the reaction between silica (SiO2) formed by oxidation of the surface and additives (Yb2O3, etc.) inside the material. The SiC ceramic of the present invention includes a surface modification layer containing silicate such as Yb2Si2O7 or Al2SiO5, and since silicate has excellent heat resistance and environmental resistance, the surface modification layer provides an excellent environmental resistant coating and has water vapor resistance of about 1,600°C.
[0038] [2] Manufacturing method of SiC ceramics The silicon carbide (SiC) ceramic of the present invention is (1) dispersing a silicon carbide-forming raw material (SiC-forming raw material) and a metal oxide in a dispersion medium; (2) sintering the dispersion obtained in step (1); (3) heat-treating the sintered product obtained in step (2) to form a surface-modified layer containing silicate on the SiC ceramic base material; The composition can be produced by a method comprising the steps of:
[0039] FIG. 1 shows one embodiment of the method for producing SiC ceramics according to the present invention.
[0040] (1) Dispersion process (sample preparation process) (1) In step (1), a base material, that is, a SiC-forming raw material, and a metal oxide are dispersed in a dispersion medium.
[0041] In the liquid phase sintering, the SiC forming raw material is SiC powder, and if necessary, a sintering aid may be added. By adding a sintering aid, it is possible to impart sufficient fracture strength even when the sintering temperature is low. The amount of sintering aid added may be, for example, about 0.1 to 25 parts by weight per 100 parts by weight of the total of the raw material powders of SiC (powdered, etc.) and metal oxide (powdered Yb2O3, etc.) contained in the dispersion. By setting the amount of sintering aid added within the above range, it is possible to satisfactorily form a surface modified layer of silicate on SiC.
[0042] In the reactive sintering method, it is preferable to use SiC powder, C powder, and Si powder. When SiC powder is used as SiC, the particle size is not particularly limited. It is preferable to use fine powder with an average particle size of about 0.02 to 20 μm for the SiC powder. The type of SiC is not particularly limited. It is preferable to use, as the SiC forming raw material, for example, β-SiC powder, which is a cubic crystal powder, α-SiC powder, which is a hexagonal crystal powder, or the like.
[0043] The metal oxide is preferably at least one metal oxide selected from the group consisting of scandium oxide (Sc2O3), yttrium oxide (Y2O3), erbium oxide (Er2O3), ytterbium oxide (Yb2O3), alumina (Al2O3), and lutetium oxide (Lu2O3).
[0044] The metal oxide is preferably a rare earth metal oxide, for example at least one metal oxide selected from the group consisting of scandium oxide (Sc2O3), yttrium oxide (Y2O3), erbium oxide (Er2O3), ytterbium oxide (Yb2O3), and lutetium oxide (Lu2O3).
[0045] The metal oxide is the raw material of silicate (Yb2SiO5, Yb2Si2O7, etc.) that forms the surface modification layer. As the metal oxide, it is preferable to use a powder of a substance that is stable in the usage environment. The raw materials SiC (powdered, etc.) and metal oxide (powdered Yb2O3, etc.) are dispersed in a dispersion medium to form a dispersion (slurry). As the dispersion medium, it is preferable to use an organic solvent such as water or alcohol (ethanol, isopropanol, etc.). The SiC forming raw material and the oxide can be uniformly dispersed in the dispersion medium. The concentration of the raw materials (SiC and metal oxide) in the dispersion (slurry) is not particularly limited. The concentration of the raw materials in the dispersion may be a concentration that is easy to process. For example, the solid content in the dispersion is preferably about 5 to 50 wt%, more preferably about 10 to 30 wt%.
[0046] (2) Sintering process (2) In step (2), the dispersion (slurry) obtained in step (1) is sintered (liquid phase sintering or the like) to obtain a SiC ceramic sintered body.
[0047] Before sintering, the dispersion (slurry) is molded into a desired shape and dried. The drying temperature and drying time can be appropriately set. The drying atmosphere can be natural drying in the air or vacuum drying.
[0048] The sintering temperature is usually set to about 1,400°C or higher. In order to impart sufficient fracture strength, the sintering temperature is preferably set to about 1,700°C or higher in the liquid phase sintering method. When a sintering aid is added, it becomes possible to set the sintering temperature lower, and even at a sintering temperature of about 1,600°C, for example, sufficient fracture strength can be imparted. The upper limit of the sintering temperature may be set to the heat resistance temperature of SiC (base material).
[0049] In the case of the reactive sintering method, pressure may be applied for molding, but pressure is not particularly required for sintering. The pressure during sintering in the liquid phase sintering method is not particularly limited. The higher the pressure during sintering, the more sufficient strength can be imparted in a short time. Usually, a pressure of about 5 MPa or more is sufficient, and a pressure of about 10 to 30 MPa is particularly preferable.
[0050] The sintering time is about 1 hour, but is set optimally depending on the shape and size of the part. The sintering atmosphere is preferably an inert gas atmosphere such as nitrogen, argon, or helium, or a reducing atmosphere.
[0051] (3) Heat treatment process (surface modification layer formation process) (3) In step (3), the sintered body obtained in step (2) is heat-treated to form a surface-modified layer containing silicate on the SiC ceramic base material.
[0052] The silicate forms a silicate according to the metal oxide added as a forming raw material. For example, depending on the type of metal oxide, scandium silicate (Sc2SiO7), yttrium silicate (Y2SiO5), erbium silicate (ErSiO5), ytterbium silicate (Yb2SiO5), ytterbium silicate (Yb2SiO7), aluminum silicate (Al2SiO5) and lutetium silicate (LuSiO5) are formed to form a surface modification layer.
[0053] The heat treatment is preferably performed in an oxidizing atmosphere such as air or steam. The heat treatment temperature is preferably about 800 to 1,700°C, more preferably about 1,100 to 1,500°C. The pressure during the heat treatment is not particularly limited. The heat treatment time is preferably about 100 hours, more preferably about 0.5 to 72 hours.
[0054] By carrying out heat treatment at a high temperature of about 1,100℃ or more, the surface of the underlying SiC (base material) is oxidized to produce silica (SiO2) as shown in the following chemical formula (1). Silica (SiO2) reacts with the raw material oxide (Yb2O3, etc.) as shown in the chemical formula (2), for example, to form a film composed of silicic acid (silicates such as Yb2Si2O7 and Yb2SiO5).
[0055] Considering the self-repairing property of the SiC ceramic of the present invention, it is sufficient that a silicate is formed in the surface modification layer. The surface modification layer preferably contains 50% by weight or more of silicate, in that the silicon carbide ceramic obtained has excellent heat resistance and environmental resistance. The upper limit of the content of silicate contained in the surface modification layer is close to 100% by weight. In this case, the surface modification layer is substantially composed of silicate. The surface modification layer preferably contains 50 to 100% by weight of silicate. In addition, the surface modification layer preferably contains 100% by weight of silicate, but may contain 50 to 80% by weight of silicate.
[0056] It is preferable to heat-treat the sintered product to form a surface-modified layer containing silicate near (or on) the surface of the SiC ceramic (base material), which is the base material. This surface-modified layer is a dense silicate layer that exhibits self-repairing properties.
[0057] SiC + 2O2 → SiO2+ CO2(1) Yb2O3+ 2SiO2 → Yb2Si2O7(2)
[0058] When the surface modification layer of the SiC ceramic of the present invention is damaged, silica (SiO2) produced by oxidation of the underlying SiC reacts with metal oxides (Yb2O3, etc.) in the SiC, and a surface modification layer of silicate (Yb2SiO5, Yb2Si2O7, etc.) is formed, thereby having the ability to self-repair the damaged coating.
[0059] The SiC ceramic of the present invention exhibits self-repairing properties because the surface modification layer is formed near (or on) the surface of the SiC ceramic (substrate) base material and is derived from the raw materials from which it is formed, i.e., all of the silicate raw materials that form the surface modification layer are contained in the SiC ceramic base material.
[0060] The above series of steps is the manufacturing process for monolithic SiC ceramics.
[0061] [3] Ceramic fiber-reinforced composite material using the above-mentioned SiC ceramics as a matrix The ceramic fiber reinforced silicon carbide composite material includes the SiC ceramic of the present invention as a base material and ceramic fibers. The SiC ceramic is a SiC ceramic containing a metal oxide, which includes a surface modified layer containing a silicate, and the surface modified layer is derived from the raw material for forming the SiC ceramic as the base material.
[0062] When using the SiC ceramics of the present invention to prepare a ceramic fiber-reinforced composite material, a green sheet can be prepared by forming the slurry into a sheet, and a ceramic fiber fabric can be layered to form a laminate. When preparing a ceramic fiber composite material, the slurry can be impregnated into a fiber fabric, or a prepreg sheet can be prepared by applying the slurry to the fiber fabric, and the prepreg sheet can be layered to form a laminate. These laminates can be finally sintered to prepare a ceramic fiber-reinforced silicon carbide composite material.
[0063] Ceramic Fiber Ceramic fibers include SiC fibers, carbon fibers (C fibers), alumina fibers, and the like.
[0064] As the SiC fiber, it is preferable to use highly crystalline SiC fiber commercially available under the trade names Tyranno SA (manufactured by Ube Industries) and Hi-Nicalon-S (manufactured by Nippon Carbon), as well as fibers with lower crystallinity. The use of highly crystalline silicon carbide fiber as the SiC fiber is particularly advantageous in terms of its high heat resistance.
[0065] Carbon fiber is an advantageous material in that it is inexpensive and does not lose strength much at high temperatures. As the alumina fiber, it is preferable to use alumina fiber commercially available under the trade names Nextel 312, Nextel 440 (manufactured by Sumitomo 3M), etc.
[0066] The shape of the ceramic fiber can be appropriately selected depending on the application and the required mechanical strength. For example, long fibers, which are continuous ceramic fibers, or short fibers cut from these can be used. It is preferable to use long fibers in order to improve the fracture toughness of the composite material. The long fibers may be continuous fibers, and there is no particular restriction on the fiber length.
[0067] It is preferable to use fibers having a length similar to that of the final composite material. If sufficient strength can be imparted to the composite material, long fibers shorter than the target composite material can also be used. Short fibers are long fibers cut into pieces. Short fibers are fibers having a length of about 1 to 10 mm.
[0068] The diameter of the ceramic fiber is not particularly limited. It is preferable to use ceramic fibers having a diameter of about 5 to 200 μm. Ceramic fibers are usually supplied as a bundle of about 500 to 2,000 fibers, or as a fiber structure such as a knitted fabric or a woven fabric using the bundle. In the present invention, such bundled ceramic fibers or fiber structures of ceramic fibers can be used depending on the shape of the target composite. From the viewpoint of efficiency in producing a ceramic fiber-reinforced composite material, it is preferable to use ceramic fibers in the form of a fiber structure such as a woven fabric.
[0069] SiC / SiC composite material The structure of the composite material is such that, when a slurry in which the powdered SiC ceramic of the present invention is dispersed in a dispersion medium is used as the raw material, and a fiber structure such as a knitted or woven fabric is used as the raw material for the SiC fiber, a layer made of SiC ceramic and the fiber structure are laminated, and some of the SiC ceramic penetrates between the SiC fibers.
[0070] When bundle-shaped SiC fibers are used as the SiC fibers, the SiC fiber bundles are embedded in the SiC ceramic. Depending on the arrangement of the SiC fibers, the composite material may have a non-reinforced portion where no SiC fibers are arranged in addition to the portion where the strength is reinforced by the SiC fibers arranged in the SiC ceramic of the present invention.
[0071] The content of the SiC fibers is not particularly limited as long as it can impart sufficient fracture strength to the composite. Based on the total material of the composite, the volume ratio of the SiC fibers is preferably about 10 to 90%, and more preferably about 30 to 70%.
[0072] In SiC / SiC composites, the bond strength between the SiC ceramics and the SiC fibers is moderately reduced. In the case of cracks occurring in the SiC ceramics, the SiC / SiC composites prevent the cracks from progressing directly to the SiC fibers, and can deflect the progression of the crack along the fiber direction. Furthermore, due to slippage at the interface with the SiC fibers and pullout of the SiC fibers, the composites exhibit behavior similar to ductility, called pseudo-ductility, and show high fracture toughness.
[0073] [4] Manufacturing method for SiC / SiC composite material The method for producing the SiC / SiC composite material is not particularly limited. The SiC / SiC composite material can be produced by the following liquid phase sintering method, reaction sintering method, or the like.
[0074] (1) Liquid phase sintering In the liquid phase sintering method, powdered raw materials are dispersed in a dispersion medium to form a slurry, which is then mixed with SiC fibers arranged in a predetermined shape to obtain a mixture to be used for sintering. The mixture is then sintered to obtain a SiC / SiC composite material.
[0075] Among the raw materials used in the liquid phase sintering method, powder may be used as the SiC ceramic of the present invention. As explained above, the SiC ceramic of the present invention contains a metal oxide. The particle size of the SiC ceramic powder is not particularly limited. The SiC ceramic powder may be fine particles within a range that allows a uniform slurry to be formed. For example, fine powder with an average particle size of about 0.02 to 20 μm may be used.
[0076] The slurry containing the powdered raw material preferably uses an organic solvent such as water or alcohol (ethanol, isopropanol, etc.) as a dispersion medium. It can be obtained by uniformly dispersing SiC ceramic powder in the dispersion medium. There is no particular limitation on the concentration of the powdered raw material in the slurry. It is sufficient to select a concentration that is easy to process. For example, the solid content is preferably about 5 to 50% by weight, and more preferably about 10 to 30% by weight.
[0077] The slurry prepared by the above method is mixed with SiC fibers to prepare a mixture to be used for sintering. As a specific method for preparing a mixture of powdered raw material and SiC fibers to be used for sintering, it is preferable to use SiC fibers as a fiber structure such as a knitted fabric or woven fabric, and apply the above slurry to the fiber structure of the SiC fibers to impregnate it.
[0078] When using bundled SiC fibers, it is preferable to put a slurry in which powdered raw material is dispersed into a mold and arrange the bundled SiC fibers in an arbitrary shape therein. In this case, the bundled SiC fibers are not limited to being arranged in one direction, but may be arranged in two intersecting directions, and it is preferable to arrange them in any other direction.
[0079] It is preferable to dry the slurry containing the powdered raw material, form it into a sheet, and laminate it with a fiber structure made of SiC fibers to prepare a mixture to be used for sintering. When using bundled SiC fibers, it is preferable to arrange the bundled SiC fibers in a manner that corresponds to the state of existence of the SiC fibers in the target composite material, and laminate the layer of the bundled SiC fibers in the arranged state and the slurry layer formed into a sheet to prepare a mixture to be used for sintering.
[0080] Depending on the thickness of the composite material to be produced, it is preferable to laminate two or more layers of the slurry and two or more layers of the SiC fibers formed into a sheet shape. In this case, it is preferable that the orientation direction of the SiC fibers is different for each layer, which can further improve the strength.
[0081] It is preferable to add powders of yttrium oxide (Y2O3), ytterbium oxide (Yb2O3), alumina (Al2O3), etc., as sintering aids to the mixture before sintering as necessary. The sintering aids may be added, for example, to a slurry containing a powdered raw material. As described above, these yttrium oxide (Y2O3), ytterbium oxide (Yb2O3), and alumina (Al2O3) are raw materials of the surface modification layer as metal oxides, and also play a role as a sintering aid. The amount of the sintering aid added is preferably about 0.1 to 25 parts by weight with respect to a total of 100 parts by weight of the raw powder of SiC ceramics contained in the slurry. By adding the sintering aid, it is possible to impart sufficient fracture strength even when the sintering temperature is low.
[0082] After preparing a mixture of SiC ceramics and SiC fibers by the above-mentioned method, the mixture can be sintered under pressure to obtain the desired SiC / SiC composite material.
[0083] The sintering temperature is usually preferably about 1,400°C or higher. In order to impart sufficient fracture strength to the SiC / SiC composite material, it is more preferably about 1,700°C or higher. When a sintering aid is added, sufficient fracture strength can be imparted even at a sintering temperature of, for example, about 1,600°C. The upper limit of the sintering temperature may be set to the heat resistance temperature of the reinforcing SiC fiber, and when highly crystalline silicon carbide fiber is used, it is preferably set to about 2,000°C.
[0084] The pressure during sintering is not particularly limited, and the higher the pressure, the more sufficient strength can be imparted in a short time. Usually, a pressure of about 5 MPa or more is sufficient, and a pressure of about 10 to 30 MPa is particularly preferable. The sintering atmosphere is preferably an inert gas atmosphere such as nitrogen, argon, or helium. In order to prevent the carbon material from being oxidized during sintering, it is preferable to sinter in an inert gas atmosphere or a reducing atmosphere.
[0085] Furthermore, a heat treatment can be carried out to form a surface modification layer.
[0086] (3) Reaction sintering In the reactive sintering method, a matrix forming material containing powder or resin containing carbon components, Si powder, and SiC powder as necessary is made into a slurry, which is mixed with SiC fibers arranged in a predetermined shape to obtain a mixture to be used for sintering, and then heated to a temperature above the melting point of silicon to react carbon and Si to form a matrix of SiC phase. The slurry contains the metal oxide contained in the SiC ceramic of the present invention. This makes the SiC fibers embedded in the matrix, and the desired SiC / SiC composite material can be obtained.
[0087] Of the raw materials for making the slurry, carbon powder is usually used as the powder containing a carbon component, but resins such as phenolic resins that carbonize below the melting point of silicon can also be used. When using resin as the powder containing a carbon component, in the process of heating to a temperature above the melting point of silicon, the resin carbonizes before reaching the melting point of silicon, 1,414°C, and then when the melting point of silicon is reached, the carbonized components of the resin react with the molten silicon to form SiC.
[0088] SiC powder may be further added to the slurry containing the raw material for forming the matrix phase. By adding the SiC powder, the SiC powder becomes a nucleus, and the SiC generated by the reaction grows around it to form a matrix. This can improve the efficiency of forming the matrix phase. The amount of the SiC powder added may be, for example, about 0.1 to 50 parts by weight with respect to 100 parts by weight in total of the powder containing the carbon component, the Si powder, and the raw material powder for forming the second phase contained in the slurry.
[0089] The particle size of each of the powder containing a carbon component, the Si powder, the SiC powder, and the metal oxide, the method of forming the slurry, etc. may be the same as in the liquid phase sintering method. There is no limitation on the mixing ratio of each component, but it is possible to form a matrix phase with a dense structure by adding an excess of Si to the carbon component. The method of preparing a mixture of the matrix phase forming raw material and the SiC fiber to be used in the reaction sintering may also be the same as in the liquid phase sintering method.
[0090] After preparing a mixture of the raw material for forming the matrix phase and the SiC fibers using the method described above, the mixture is heated to a temperature above the melting point of silicon to react carbon and Si, thereby forming SiC and forming a matrix with a multiphase structure including a SiC phase and a second phase.
[0091] The heating temperature may be set to about 1,414°C, which is the melting point of silicon, or higher, but in order to provide sufficient fracture strength, it is preferably set to about 1,450°C or higher. The upper limit of the heating temperature may be set to the heat resistance temperature of the SiC fiber to be reinforced, and when highly crystalline silicon carbide fiber is used, it is preferably set to about 2,000°C. The heating atmosphere is preferably a vacuum atmosphere. An inert gas atmosphere such as nitrogen, argon, or helium is preferably used.
[0092] Furthermore, a heat treatment can be carried out to form a surface modification layer.
[0093] Excellent environmental resistance due to the surface modification technology of this invention The present invention is a technology for forming a surface-modified layer of silicate (Yb2SiO5, Yb2Si2O7, etc.) with excellent water vapor resistance on the surface of SiC by a method completely different from conventional PVD (physical vapor deposition), etc. In other words, in the SiC ceramics of the present invention, SiC (base material) is surface-modified with silicate (Yb2SiO5, Yb2Si2O7, etc.).
[0094] The SiC ceramics of the present invention include those having excellent high-temperature water vapor resistance coating even without providing a water vapor resistant layer of BSAS (1-xBaO-xSrO-Al2O3-2SiO2, 0≦x≦1). In the SiC ceramics of the present invention, if the thermal expansion coefficients of SiC and silicate are close to each other, the thermal expansion coefficient difference between SiC and silicate is relaxed without providing a thermal expansion coefficient difference relaxation layer such as BSAS+Mullite (3Al2O3·2SiO2). In addition, the SiC ceramics of the present invention is excellent in that it does not require a thermal expansion coefficient difference relaxation layer, for example, when Yb2Si2O7 is included as the main component of the silicate, since the thermal expansion coefficients of SiC and silicate are close to each other and the difference in thermal expansion coefficient between the base material and the surface modification layer is small.
[0095] Conventional coating techniques have not been able to adequately bond an environmentally resistant coating, such as a water vapor resistant coating, to a SiC substrate. For this reason, a bonding layer that also functions as an oxidation-resistant coating, such as Si, has been formed, and then a bonding layer and a thermal expansion buffer layer for the environmentally resistant coating have been formed on top of the bonding layer to form an environmentally resistant coating layer. In the present invention, the surface of the base material is directly converted into a surface modification layer, so no bonding layer is required.
[0096] The SiC ceramics of the present invention can be prepared simply and at low cost, without requiring a costly and complicated multilayer coating, and the surface of the SiC base material can be modified with silicate only by heat treatment. The SiC ceramics of the present invention form a surface modified layer (coating layer) of silicate by directly oxidizing the surface of SiC, so there is no need to add an additional surface modified layer from the outside. The SiC ceramics of the present invention can be controlled so that a SiO2 layer is not formed between SiC and the silicate (surface modified layer) on its surface, and when a SiO2 layer is not formed, there is no risk of cracks developing due to the SiO2 layer. Even if the surface modified layer of the SiC ceramics of the present invention peels off or cracks are generated in the surface modified layer, a new surface modified layer of silicate is formed by oxidation, and the SiC ceramics of the present invention have self-repairing properties.
[0097] The surface modification technique of the present invention is based on the reaction of metal oxide (Yb2O3, etc.) with SiO2 (a reaction product of SiC and oxygen), and therefore a dense surface modification layer can be formed. When the SiC ceramic of the present invention includes a surface modification layer containing silicate such as Yb2Si2O7 or Al2SiO5, it is expected to have water vapor resistance of about 1,600°C. The surface modification technique of the present invention can be performed only by heat treatment, and when combined with a BN particle-dispersed SiC composite material (Yb2Si2O7), it is possible to prepare a simple and low-cost water vapor-resistant SiC composite material. By combining a BN particle-dispersed composite material with excellent oxidation resistance and an oxide (Yb2O3, etc.), a surface modification layer of silicate (Yb2Si2O7) can be formed on the surface of the BN particle-dispersed composite material as a high-temperature water vapor-resistant material.
[0098] Conventional SiC composite materials required an oxidation-resistant Si layer and a thermal expansion coefficient mitigation layer, and had the problem of the coating peeling off due to oxidation of the Si layer when cracks occurred.
[0099] In the SiC ceramics of the present invention, the silicate (Yb2Si2O7, etc.) contained in the surface modification layer has a similar thermal expansion coefficient to SiC, so even if the intermediate layer of the thermal expansion coefficient relaxation layer that was previously required is omitted, interfacial peeling of the surface modification layer caused by the difference in thermal expansion is unlikely to occur. In addition, the present invention can directly form a surface modification layer by a chemical reaction on the surface without the Si layer, which is a bonding layer for bonding the coating layer that also serves as an oxidation-resistant coating to the SiC base material.
[0100] The SiC ceramics of the present invention can also be applied to composite materials with SiC as the matrix (C fiber-reinforced SiC composite material (C / SiC), SiC fiber-reinforced SiC composite material (SiC / SiC), etc.). For example, an excellent composite material can be produced by adding an oxide (Yb2O3, etc.) to a SiC / SiC matrix to form a silicate (Yb2Si2O7) on the surface. In this case, it is sufficient that the oxide (Yb2O3, etc.) is contained not in the entire matrix, but at least near the surface of the matrix, that is, it is sufficient that the oxide (Yb2O3, etc.) is contained in a part of the matrix.
[0101] When a coating thicker than the coating layer formed by the surface modification of the present invention alone is required, it is possible to combine the surface modification technique of the present invention with a conventional coating technique. If the surface modification technique of the present invention is used, if the environmentally resistant coating is the same as the surface modification material, it can be directly coated because there is no difference in thermal expansion coefficient, and the bonding layer and the thermal expansion coefficient relaxation layer can be omitted. For example, this technique is an embodiment in which Yb2Si2O7 is formed on the silicon carbide ceramic, which is the base material, using the surface modification technique of the present invention, and Yb2Si2O7 is coated on it using an existing technique. This technique is a preferred embodiment in terms of practicality. EXAMPLES
[0102] The present invention will be described in detail below with reference to examples.
[0103] Example 1 SiC ceramics were manufactured through the steps of: (1) dispersing SiC and metal oxide in a dispersion medium; (2) sintering the dispersion obtained in step (1); and (3) heat-treating the sintered material obtained in step (2) to form a surface modification layer containing silicate on the SiC ceramic base material.
[0104] Metal oxide: Ytterbium oxide (Yb2O3) Sintering conditions: 1,850℃, 20MPa, 1 hour Heat treatment conditions: 1,350℃, in air or water vapor, 24 hours Silicates: Ytterbium Silicate (Yb2Si2O7)
[0105] Figure 2 shows a comparison of the liquid phase sintered SiC using Yb2O3 (sintering aid) of the embodiment after heat treatment (1,350℃-24h). Examples of sintering aids and metal oxides include Al2O3 and Yb2O3. Yb2O3 is a metal oxide that also functions as a sintering aid in liquid phase sintering and forms a surface modification layer as a surface modification.
[0106] In Fig. 2, the content of silicate contained in the surface modification layer of each example is shown. When a dispersion of SiC (Yb-SiC6) containing 6 wt% Yb2O3 was liquid phase sintered and then heat treated in an air atmosphere, the content of silicate (Yb2Si2O7) contained in the surface modification layer was 50 vol% (volume %) based on the image analysis. When heat treated in a water vapor atmosphere, the content of silicate (Yb2Si2O7) contained in the surface modification layer was 79 vol% based on the image analysis.
[0107] When a SiC dispersion containing 20 wt% Yb2O3 (Yb-SiC20) was liquid phase sintered and then heat-treated in an air atmosphere, the silicate (Yb2Si2O7) content in the surface modification layer was 60 vol% based on the image analysis.When heat-treated in a water vapor atmosphere, the silicate (Yb2Si2O7) content in the surface modification layer was 53 vol% based on the image analysis.
[0108] The SiC ceramic of the present invention contains a surface modified layer containing a metal oxide and a silicate, and the surface modified layer is derived from the raw material of the SiC ceramic, which is the base material. Therefore, for the SiC ceramic of the present invention, the "vol% (volume%)" measured based on the image analysis in the examples may be converted to "wt% (weight%)".
[0109] Figure 3 shows the structure of the liquid phase sintered SiC using the Yb2O3 (sintering aid) of the embodiment after heat treatment (20w% material, 1,350℃-24h). Figure 4 shows the composition analysis of the liquid phase sintered SiC using the Yb2O3 (sintering aid) of the embodiment after heat treatment (20w% material, 1,350℃-24h).
[0110] Example 2 SiC ceramics were manufactured through the steps of: (1) dispersing SiC, C, Si, and metal oxide in a dispersion medium; (2) sintering the dispersion obtained in step (1); and (3) heat-treating the sintered material obtained in step (2) to form a surface modification layer containing silicate on the SiC ceramic base material.
[0111] Metal oxide: Ytterbium oxide (Yb2O3) Sintering conditions: 1,460℃, 2 hours Heat treatment conditions: 1,350℃, in air, 24 hours Silicates: Ytterbium Silicate (Yb2Si2O7)
[0112] FIG. 5 shows a composition analysis of the reaction sintered SiC using the Yb2O3 metal oxide of the embodiment after heat treatment.
[0113] Example 3 The SiC fiber-reinforced composite material was manufactured through the steps of: (1) dispersing SiC, BN, and metal oxide in a dispersion medium; (2) impregnating SiC fibers with the dispersion obtained in step (1) to form a prepreg sheet; (3) stacking and sintering the prepreg sheets obtained in step (2); and (4) heat-treating the sintered product obtained in step (3) to form a surface modification layer containing silicate on the SiC fiber-reinforced composite material base material.
[0114] Metal oxide: Ytterbium oxide (Yb2O3) Sintering conditions: 1,890℃, 20MPa, 1 hour Heat treatment conditions: 1,500℃, in air, 100 hours Silicates: Ytterbium Silicate (Yb2Si2O7)
[0115] Figure 6 shows the composition analysis of the liquid phase sintered SiC fiber reinforced composite material using the Yb2O3 metal oxide of the embodiment after heat treatment. Yb2O3 is a metal oxide that also functions as a sintering aid in liquid phase sintering and forms a surface modification layer as a surface modification agent.
[0116] Excellent environmental resistance due to the surface modification technology of this invention The SiC ceramics of the present invention can be surface-modified to form a silicate layer (surface-modified layer) simply by subjecting the sintered body to further heat treatment (oxidation treatment).Compared to the conventional technology, the present invention does not require the installation of many devices and can reduce energy and costs.
[0117] The SiC ceramic of the present invention is a technology different from the film formation by the coating technology of the conventional technology, since the silicate constituting the surface modification layer is derived from the SiC of the SiC ceramic. According to the present invention, there is no risk of the surface modification layer containing silicate peeling off at the interface with the SiC (base material). The SiC ceramic containing the metal oxide of the present invention has a surface modification layer derived from the SiC ceramic, which is the base material, that is, it is a silicate layer (surface modification layer) derived from the SiC ceramic, which is the base material, and even if the silicate surface modification layer peels off, it is capable of self-repair.
Claims
1. 1. A method for producing silicon carbide ceramics, comprising: (1) dispersing a silicon carbide forming raw material and a metal oxide in a dispersion medium; (2) sintering the dispersion obtained in step (1) at 1400 to 1890° C.; (3) A step of heat treating the sintered product obtained in the step (2) at 1100 to 1700° C. in an oxidizing atmosphere to form a surface modified layer containing silicate on the silicon carbide ceramic base material; A method for producing silicon carbide ceramics (excluding silicon carbide ceramics containing a rare earth silicide consisting only of rare earth and silicon), comprising: Where: The silicate content in the surface modification layer is 50% by weight or more, The silicon carbide ceramic contains a metal oxide, which is a raw material for forming the silicon carbide ceramic, The metal oxide consists of only the following (a) or (b): (A) Scandium oxide (Sc 2 O 3 ), yttrium oxide (Y 2 O 3 ), erbium oxide (Er 2 O 3 ), ytterbium oxide (Yb 2 O 3 ) and lutetium oxide (Lu 2 O 3 ) and alumina (Al 2 O 3 ), (A) one selected from the group consisting of scandium oxide (Sc 2 O 3 ), yttrium oxide (Y 2 O 3 ), erbium oxide (Er 2 O 3 ), ytterbium oxide (Yb 2 O 3 ), and lutetium oxide (Lu 2 O 3 ); When the metal oxide is composed only of (A), the silicate is composed only of the following (C) or (D): When the metal oxide consists only of the above (A), the silicate consists only of the following (D): (c) one selected from the group consisting of scandium silicate (Sc 2 Si 2 O 7 ), yttrium silicate (Y 2 SiO 5 ), erbium silicate (ErSiO 5 ), ytterbium silicate (Yb 2 SiO 5 ), ytterbium silicate (Yb 2 Si 2 O 7 ) and lutetium silicate (LuSiO 5 ), and aluminum silicate (Al 2 SiO 5 ); (D) One selected from the group consisting of scandium silicate (Sc 2 Si 2 O 7 ), yttrium silicate (Y 2 SiO 5 ), erbium silicate (ErSiO 5 ), ytterbium silicate (Yb 2 SiO 5 ), ytterbium silicate (Yb 2 Si 2 O 7 ) and lutetium silicate (LuSiO 5 ).
2. The method of claim 1 , wherein the surface modification layer comprises a silicate.
3. 3. The method according to claim 1, wherein the step (3) is a step of heat-treating the sintered product obtained in the step (2) to form a surface-modified layer containing a silicate on the surface of the silicon carbide ceramic base material.
4. The method according to any one of claims 1 to 3, wherein the metal oxide consists only of the following (A) and the silicate consists only of the following (D): (A) one selected from the group consisting of scandium oxide (Sc 2 O 3 ), yttrium oxide (Y 2 O 3 ), erbium oxide (Er 2 O 3 ), ytterbium oxide (Yb 2 O 3 ), and lutetium oxide (Lu 2 O 3 ); (D) Scandium silicate (Sc 2 S 2 O 7 ), yttrium silicate (Y 2 SiO 5 ), erbium silicate (ErSiO 5 ), ytterbium silicate (Yb 2 SiO 5 ), ytterbium silicate (Yb 2 S 2 O 7 ) and lutetium silicate (LuSiO 5 ) A type selected from the group consisting of.
Citation Information
Patent Citations
liquid-phase compacted silicon carbide ceramics with high oxidation resistance in humid atmospheres
DE10342580A1
Rare earth silicate coating film applied to silicon-based ceramic part for improving corrosion resistance by controlled oxidization
JP2001146492A
Rare earth silicate high temperature steam corrosion preventing coating film and method of manufacturing the same
JP2004299948A
Silicon carbide ceramic member with oxide layer
JP2006514912A
Composite refractory and production method thereof
JP2015171985A
